2023
DOI: 10.2174/1574887118666230227113217
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Superficial Trigeminal Nerve Blocks are not More Effective than a Placebo in Abolishing Post-operative Headache Pain in Pituitary Transsphenoidal Neurosurgery: A Prospective, Randomized, Doubleblinded Clinical Trial

Abstract: Background: Pituitary neurosurgery executed via the transsphenoidal endonasal approach is commonly performed for pituitary adenomas. Reasons for prolonged hospital stay include postoperative headache and protracted nausea with or without vomiting. Bilateral superficial trigeminal nerve blocks of the supra-orbital V1 and infra-orbital V2 (SION) nerves performed intra-operatively as a regional anesthetic adjunct to general anesthesia were hypothesized to decrease 6 hours postoperative morphine PCA (patient-contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Patients also reported a higher satisfaction score in the block group 52 . However, another study found that there was no statistical difference in morphine use between placebo and block groups, and that the block group had higher postoperative pain scores and delayed postanesthesia care unit discharge 53 . Another study conducted by Mariano et al 54 demonstrated lower postoperative pain scores in the block group, supporting the potential benefits of the block.…”
Section: Infraorbital Nerve Block For Pituitary Surgerymentioning
confidence: 96%
“…Patients also reported a higher satisfaction score in the block group 52 . However, another study found that there was no statistical difference in morphine use between placebo and block groups, and that the block group had higher postoperative pain scores and delayed postanesthesia care unit discharge 53 . Another study conducted by Mariano et al 54 demonstrated lower postoperative pain scores in the block group, supporting the potential benefits of the block.…”
Section: Infraorbital Nerve Block For Pituitary Surgerymentioning
confidence: 96%